LEVERAGING INFORMATION TECHNOLOGY FOR ENHANCED GOVERNMENT SERVICE EFFICIENCY IN LINGGA REGENCY - Nurhayati, Nurhayati; Jufri, M.; hajar, Siti; Sari, Nuzuliana Anggar; Apriansyah, M. Ramdan (PENANOMICS: International Journal of Economics, 2024)
This study investigates the impact of information technology on the effectiveness of government services in Lingga Regency, focusing on the role of technological infrastructure, information technology usage, and government policy support. A quantitative approach was employed, using total sampling with 30 employees from the North Lingga District Office as respondents. Data were analyzed using Smart PLS to test the relationships between variables. The results show that both the quality of technological infrastructure and the use of information technology have a significant positive effect on the effectiveness of government services. Furthermore, government policy support was found to moderate the relationship between infrastructure quality and service effectiveness, enhancing the impact of infrastructure investments on public service delivery. However, the moderating effect of policy support on the use of IT was weaker, indicating that IT can directly improve service effectiveness without extensive policy intervention. These findings highlight the importance of investing in both infrastructure and IT, while also developing supportive policies to sustain long-term improvements in government services. This research provides practical insights for policymakers and government officials in optimizing public administration through strategic technology integration.